Thermal behaviour of stirred yoghurt during cooling in plate heat exchangers - Fernandes, C. S. (2006)
In this study, CFD calculations were made in order to analyse the thermal behaviour of yoghurt in a plate heat exchanger, the yoghurt viscosity being described by a Herschel–Bulkley model. The influence of Reynolds number on local Nusselt numbers was analysed as well as the influence of entry effects on average Nusselt number. Numerical runs considering and discarding the influence of temperature on the viscosity were performed and the impact on average Nusselt numbers was analysed. Transversal variations of viscosity were studied and thermal correlations including the ratio between bulk and wall viscosities are proposed. The obtained thermal correlations were compared with the experimental ones (described in the literature) and a very good agreement was found, mainly when considering the effect of temperature on viscosity. Simulations with a non-Newtonian fluid having lower Prandtl numbers than yoghurt were performed in order to analyse the influence of this variation on the Reynolds number exponent of the thermal correlation